Advancing the historical geography of late Ottoman and British Mandate Palestine using GIScience: A review. Issue 6 (27th July 2020) - Zohar, Motti
Abstract: Late Ottoman Empire and Mandate Palestine are two important periods preceding independent Israel, characterized by increased attention to Palestine along with modernization processes and substantial landscape changes. Significant increase is also noted in survey and mapping, resulting in a wealth of visual sources. However, while textual sources were used intensively in various studies, the latter were analyzed to a much lesser extent. A major discipline based on the study of visual sources is historical geography. However, lately it seems that historical geography worldwide seeks for new approaches while struggling to retain dominancy in an environment becoming more computerized and technological. In this article I review the opportunities, pitfalls, and challenges of incorporating GIScience into the historical geography of late Ottoman and Mandate Palestine. Accordingly, it is suggested that a proper integration will contribute a substantial theoretical and methodological novelty while boosting the discipline of historical geography as well as other social sciences and humanities disciplines.